Substrate pH Influences the Nutrient Absorption and Rhizosphere Microbiome of Huanglongbing-Affected Grapefruit Plants - Ferrarezi, Rhuanito Soranz; Lin, Xiongjie; Gonzalez Neira, Andres C.; Tabay Zambon, Flavia; Hu, Hanqing; Wang, Xianda; Huang, Jing-Hao; Fan, Guocheng (Frontiers in Plant Science, 2022)
The substrate pH directly affects nutrient availability in the rhizosphere and nutrient uptake by plants. Macronutrients such as nitrogen, potassium, calcium, magnesium, and sulfur are highly available at pH 6.0–6.5, while micronutrients become less available at higher, alkaline pH (pH > 7.0). Recent research has indicated that low pHs can enhance nutrient uptake and improve sweet orange (Citrus sinensis) tree health. We designed a study to understand the influence of a wide range of substrate pH values on plant size and biomass, nutrient availability, leaf gas exchange, and rhizosphere microbiome of grapefruit (Citrus paradisi) affected by Huanglongbing (HLB). Two-year-old “Ray Ruby” grapefruit plants grafted on sour orange (Citrus aurantium) rootstock were cultivated indoors in 10-cm wide × 40-cm tall pots with peat:perlite commercial substrate (80:20 v/v). We tested two disease statuses [HLB-free or healthy (negative, HLB–) and HLB-affected (positive, HLB+)] and six substrate pH values (4, 5, 6, 7, 8, 9) in a 2 × 6 factorial arranged on a complete randomized design with four replications. The canopy volume of HLB+ plants was 20% lower than healthy plants, with pHs 7 and 9 resulting in 44% less canopy volume. The root and shoot ratio of dry weight was 25.8% lower in HLB+ than in healthy plants. Poor root growth and a decrease in fibrous roots were found, especially in pH 5 and 6 treatments in HLB+ plants (p < 0.0001). The disease status and the substrate pHs influenced the leaf nutrient concentration (p < 0.05). High substrate pH affects nutrient availability for root uptake, influencing the nutrient balance throughout the plant system. pH values did not affect plant photosynthesis, indicating that pH does not recover HLB+ plants to the photosynthetic levels of healthy plants—even though high pH positively influenced internal CO2. There were collectively over 200 rhizobacterial identified by the 16S rRNA gene sequencing in individual phylogenetic trees. Most rhizobacteria reads were identified in pH 9. Our results indicated no effect of substrate pHs on the plant disease status induced by enhanced nutrient uptake.